A Systematic Review of Inter-ethnic Variability in Facial Dimensions - Fang, Frank (2011)
BACKGROUND: The earliest recorded facial proportional analysis is in the Greek neoclassical canons (c. 450 B.C.). In contemporary times, there has not yet been a study that describes the relative differences in facial proportions among the world’s different ethnic groups. The specific aim of this project is to perform a systematic review of data from the existing literature in order to evaluate the degree of variability in the facial dimensions among various ethnic groups. METHODS: A PubMed database review identified primary articles containing measurements of facial proportions from various ethnic groups. Data extracted from these articles were the actual means and standard deviations of recorded facial measurements. These facial measurements included the heights and widths of the upper, middle, and lower face which are the features originally described by the neoclassical canons. Coefficients of variation (CV) were calculated to derive a unit-free comparison of the degree of variability among different ethnic groups in each of the neoclassically-measured facial dimensions. RESULTS: Our literature search identified 239 potential articles. After screening for the inclusion and exclusion criteria, seven relevant articles were selected. These articles contained data on 11 linear facial measurements from 2359 male and female individuals from 27 different ethnic groups. 95% confidence intervals of the CVs of the measurements indicated that the features that demonstrated the largest differences between the different ethnic populations are the forehead height, interocular distance, and nasal width. The least amount of variability is found in the ear height and upper, middle, and lower facial widths. CONCLUSIONS: The greatest inter-ethnic variability in facial proportions exists in the height of the forehead. More pronounced difference among the ethnic groups is also present in the measurements of the eyes, nose, and mouth. There is no significant difference between sexes in the neoclassical facial proportions.